Socio-demographic factors associated with mental health disorders among rural women in Mymensingh, Bangladesh - Khan, Rizwana; Akter, Fahmida; Rahman, Musarrat; Amin, Nuhu; Rahman, Mahbubur; Winch, Peter J. (Frontiers in Psychiatry, 2025)
IntroductionIn Bangladesh, the reported prevalence of mental disorders among adults varies from 6.5% to 31.0%. This study aims to identify the socio-demographic factors associated with mental health disorders among rural women in Bangladesh.MethodWe enrolled 401 adult women from four sub-districts of Mymensingh district, Bangladesh. To determine the factors involved, we employed a modified version of the mental state examination (MSE) scale, in addition to questionnaires focusing on socio-demographic information, health, and well-being.ResultThe prevalence of mental health problems, measured by the MSE scale, was 26%. Even after controlling for potential confounders such as respondent's age, education level, spouse's schooling, household income, health status, domestic violence, family disharmony, social security, and support, household income remained significantly associated with behavioral problems. Individuals with higher incomes experience a lower prevalence of mental health disorders (Prevalence Ratio [PR] = 0.48; 95% CI 0.27-0.86). Poor physical health significantly correlated with behavior and mood (PR = 0.77; 95% CI 0.61-0.98). Older respondents encountered more challenges related to memory (PR = 1.42; 95% CI 1.13-1.79).DiscussionThese findings highlight the crucial role of addressing socio-demographic factors, like income and physical health, when promoting mental health among rural women in Bangladesh. By acknowledging and targeting these factors, interventions can be more tailored and effective, ensuring improved well-being and resilience within this population.